2016
DOI: 10.1115/1.4034689
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exit Pressure Pulsation on the Performance and Stability Limit of a Turbocharger Centrifugal Compressor

Abstract: It is well known that compressor surge imposes a significant limit on the flow range of a turbocharged internal combustion engine. The centrifugal compressor is commonly placed upstream of the inlet manifold, and hence, it is exposed to the intermittent flow regime of the inlet valves. Surge phenomena have been well studied over the past decades, and there still remains limited information with regard to the unsteady impact caused by the inlet valves. This study presents an experimental evaluation of such a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Marelli et al 10,11 used the Variable Valve Actuation (VVA) system to generate pressure waves resembling that in real engines.It is found that a hysteresis loop is formed and the compressor surge boundary will shift during the transients. Barrera-Medrano et al 12 adopted a rotary valve to simulate the pressure pulsation,similar results are found that the compressor operating point can go beyond the surge boundary. Galindo et al 13 investigated the influence of different pipeline designs at the compressor downstream.Results indicate that the pressure pulsation amplitude is greatly dependent on the pipe length.…”
Section: Introductionmentioning
confidence: 76%
“…Marelli et al 10,11 used the Variable Valve Actuation (VVA) system to generate pressure waves resembling that in real engines.It is found that a hysteresis loop is formed and the compressor surge boundary will shift during the transients. Barrera-Medrano et al 12 adopted a rotary valve to simulate the pressure pulsation,similar results are found that the compressor operating point can go beyond the surge boundary. Galindo et al 13 investigated the influence of different pipeline designs at the compressor downstream.Results indicate that the pressure pulsation amplitude is greatly dependent on the pipe length.…”
Section: Introductionmentioning
confidence: 76%
“…Galindo et.al [17] shows in the experiment that remarkable improvement of surge margin up to 15% can be achieved by the pulsating backpressure depending on the rotational speed of the compressor. Barrera-Medrano et.al [18] further demonstrates that the influence is also coupled with the volume of pipes at compressor exit.…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, [19] specified certain parameters for the objective function, including pressure ratio, efficiency and thrust, and changed the impeller profile from the hub to shroud, resulting in incredible improvements, including an efficiency increase of 4.5% and a pressure ratio increase of 16%. Investigating the effect of exit pressure pulsation on the performance and stability limit of a turbocharger centrifugal compressor, [20] showed that the presence of a volume in the system exerts the most significant effect on the surge margin of the compressor under unsteady conditions. Optimizing the aerodynamic design of the impellers of a centrifugal compressor using an inverse method based on the meridional viscous flow analysis [21] resulted in performance improvements and suppression of flow separations on the suction surfaces in the optimal design cases.…”
Section: Introductionmentioning
confidence: 99%